Barriers to voting and the cost of voting among low socioeconomic, young and migrant voters in New Zealand. (2nd January 2018) - Galicki, Celestyna
ABSTRACT: Downs' concept of the cost of voting emphasises time, information and money. These costs remain central to the understanding of cost of voting. However, in this study conducted in Auckland, New Zealand, young, migrant and low-socioeconomic focus group participants, when asked about the costs of voting that make a difference for their turnout decision, pointed more often to intangible, psychological costs. These costs include risk (such as concerns about debt collectors using the electoral roll) or not being able to express oneself in the preferred way (e.g. the ban on voting booth selfies). The data also shows that some voters attach meanings to the act of voting that go beyond lending support to a political party or candidate – voting can be viewed as an act of belonging or acceptance of the 'system'. These findings suggest that intangible costs of voting are important for some voters. In this article, I discuss the implications of these findings for election administration reform in New Zealand and I also apply the sociological institutionalist approach to discuss what these findings mean for our understanding of the cost of voting.